101 Pat-Downs An Undercover Look at Airport Security and the TSA. - Redden, Shawna Malvini (Potomac Books, 2021)
101 Pat-Downs traces the history of airport security since September 11, 2001, introducing assorted characters of airport security, from passengers who check their brains with their baggage to Transportation Security Administration officers who break the stereotypes.